An Observational Study of the Clinical Profile of Congenital Hypothyroidism in Children. - Joseph, Shiji; Mathews, Lulu; M, Vijayakumar (Asian Journal of Medical Research, 2019)
Background: Thyroid hormones are important for the general growth and development of the infant and the child, particularly in the differentiation and function of the nervous system. They are essential in the maturational events involved in the transition of the neonate to the adult. Subjects and Methods: The prospective, observational study was conducted in Department of Pediatrics, Institute of Maternal and Child Health, Calicut Medical College for a period of two years. After getting informed consent from the parents, history was taken followed by physical and systemic examination of the baby. Physical and systemic examination was done. Anthropometric measurements were taken and laboratory investigations were done. Results are expressed in terms of frequencies and means. Data is analyzed using SPSS. Results: Congenital hypothyroidism is often diagnosed very late. Mean age at diagnosis was 1.32 year in the present study. Birth weight may not be a clinically useful indicator of congenital hypothyroidism. Absence of classical clinical features in the new born period is the major reason for the delay in diagnosis. With delay in diagnosis of congenital hypothyroidism the predominant clinical features are those of prolonged hypothyroid state like microcephaly, short stature, macroglossia, dry skin and delayed bone age. Conclusion: Any child with facial puffiness, recent onset poor scholastic performance or excessive sleepiness with or without goiter should be suspected to have juvenile hypothyroidism and evaluated.